The Competence Paradigm in Education applied to the Multicomponent Models of Translator Competences. - Plaza-Lara, Cristina (My University, 2016)
The concept of competence in Translation Studies has been fundamental to many publications that have shed light on its definition, acquisition, components, etc. In recent decades, the amount of research on multicomponential models of translator competences has grown considerably and the main components of translator competence have been established. Some researchers only list the main constituent parts, but others try to establish all the components in extensive lists of skills. Translation Studies, as an interdisciplinary field, must take into consideration the studies carried out in other related sciences in order to expand and enrich the research. The concept of competence is closely linked to education and that is the main reason why we believe that theories from this field should be applied to the studies carried out on translator competence. Three main approaches have traditionally influenced this concept in education: the behaviourist, the functional and the constructivist approaches. In this article we will analyse these theories, along with multicomponential models of translator competences, in order to draw conclusions on how they should influence how the concept is understood.
Keywords: Traducción - Estudio y enseñanza superior; Translator competence; Multicomponential models; Constructivist approaches; Competences in education